Psychological distress and mental health service contact of unaccompanied asylum‐seeking children. Issue 5 (7th June 2012) - Sanchez‐Cao, E.; Kramer, T.; Hodes, M.
Abstract Background Evidence is emerging that psychological problems, particularly symptoms of depression and post‐traumatic stress disorder, are more prevalent in unaccompanied asylum‐seeking children (UASC) than their accompanied peers. However, little is known about help seeking and mental health service (MHS) utilization in this group, and how this relates to their psychological needs. This study aims to describe the level of psychological distress among a group of UASC and the pattern of MHS contact. Method Socio‐demographic data on 71 UASC residing in London was obtained and self‐report questionnaires were completed regarding trauma events (Harvard Trauma Questionnaire), general psychological distress [Strengths and Difficulties Questionnaire (SDQ)], post‐traumatic stress symptoms (Impact of Event Scale), depressive symptoms (Birleson Depression Self‐Rating Scale for Children) and contact with MHS (Attitudes to Health and Services Questionnaire). Results UASC were mainly male (n = 48, 67.6%), Black African (n = 39, 54.9%) and their median age was 17 years (interquartile range = 15; 17). They had been living in the UK for a median of 18 months. Eight (11.3%) scored on the SDQ borderline/abnormal range for total symptoms, but this was 21 (29.6%) using the SDQ emotional subscale. Forty‐seven (66.2%) were at high risk for post‐traumatic stress disorder and nine (12.7%) at high risk for depressive disorder. Only 12 (17%) had MHS contact. Predictors of MHS contact were depressive symptoms and duration of time in the UK. Conclusions UASC had a high level of emotional symptoms, especially post‐traumatic stress symptoms. However, only a small proportion of UASC were in contact with MHS. This suggests a high level of MHS under‐utilization, and reasons for this are discussed.